Buddha and Kalki avatara of Vishnu -022.JPG - Saurabh Saxena (2022)
Image courtesy : Saurabh Saxena - https://puratattva.in/ Buddha is considered to be the 9th Avatar of Vishnu. Here the two hands of the deity are holding Shankha and Chakra. The other two hands are in the meditative posture similar to Buddha. Though the sculpture next to Budhha does not exhibit any distinct iconographic details, it could be Kalki - the 10th Avatara of Buddha.